Di balik hasil panen berlimpah: Bahaya pestisida kimia bagi kesehatan masyarakat dan lingkungan - Lu'ai, Yusril Zam Zami (Maliki Interdisciplinary Journal, 2025)
Pesticides are chemicals created as a form of modern agricultural innovation. The use of pesticides has become a common way in modern agriculture to control pests and plant diseases in order to increase crop yields. However, the use of pesticides can have a negative impact on the environment and the health of people who consume the harvest. The environment can especially affect soil fertility and water quality around agricultural areas. And it disrupts health which can trigger diseases such as cancer, infertility, liver disease, body defects and other chronic diseases. This study aims to increase public awareness of the importance of maintaining the health and ecosystem of the surrounding environment, one of which is by using pesticides wisely and innovating to create a healthier and more sustainable environment.